Tailoring porosity and rotational dynamics in a series of octacarboxylate metal-organic frameworks - Moreau, Florian; Kolokolov, Daniil L.; Stepanov, Alexander G.; Easun, Timothy L.; Dailly, Anne; Lewis, William; Blake, Alexander J.; Nowell, Harriett; Lennox, Matthew J.; Besley, Elena; Yang, Sihai; Schröder, Martin (National Academy of Sciences, 2017)
Modulation and precise control of porosity of metal-organic frameworks (MOFs) are of critical importance to their materials function. Here we report the first modulation of porosity for a series of isoreticular octacarboxylate MOFs, denoted MFM-180 to MFM-185, via a strategy of selective elongation of metal-organic cages. Owing to the high ligand connectivity, these MOFs show absence of network interpenetration, robust structures and permanent porosity. Interestingly, activated MFM-185a shows a record high BET surface area of 4734 m2 g-1 for an octacarboxylate MOF. These MOFs show remarkable CH4 and CO2 adsorption properties, notably with simultaneously high gravimetric and volumetric deliverable CH4 capacities of 0.24 g g-1 and 163 v/v (298 K, 5-65 bar) recorded for MFM-185a due to selective elongation of tubular cages. Dynamics of molecular rotors in deuterated MFM-180a-d16 and MFM-181a-d16 were investigated by variable-temperature 2H solid state NMR spectroscopy to reveal the reorientation mechanisms within these materials. Analysis of the flipping modes of the mobile phenyl groups on the linkers, their rotational rates and transition temperatures, paves the way to controlling and understanding the role of molecular rotors through organic linker design within porous MOF materials.